EXPLORING SILVER EMPLOYMENT OPPORTUNITIES FOR ECONOMICALLY VULNERABLE OLDER ADULTS IN MALAYSIA: A QUALITATIVE STUDY - Minhat, Halimatus Sakdiah; Foong, Hui Foh (Malaysian Journal of Public Health Medicine, 2026)
Longevity may impose substantial financial burdens, particularly among economically vulnerable older adults. Silver employment represents an important component of active ageing and a potential strategy to address challenges associated with population ageing. This qualitative study aimed to explore potential silver employment opportunities for economically vulnerable older adults in Malaysia. In-depth interviews and focus group discussions (FGDs) were conducted among 21 older adults aged 55 years and above, recruited using convenience and snowball sampling techniques. Data collection continued until thematic saturation was achieved. Interviews and FGDs were guided using a validated semi-structured interview protocol containing predetermined questions and prompts, with flexibility to explore emerging themes. All interviews were audio-recorded, transcribed verbatim, and analysed using Braun and Clarke’s thematic analysis approach. Four major themes emerged: (i) centralised database/portal/advisory system, (ii) reskilling and upskilling, (iii) paid grandparenting, and (iv) community empowerment and incentive-based employment. The findings highlight the urgent need to strengthen silver employment opportunities for economically disadvantaged older adults through structured and sustainable mechanisms. Effective implementation requires active collaboration among relevant stakeholders, continuous policy support, and greater attention to barriers such as the digital divide among older adults.